PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE (AI) BAGI GURU PENJAS - Marsuki, Marsuki; Torano, Fazryani Mazita; Hidayah, Hidayah (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
This training is entitled “Training on Making Artificial Intelligence (AI)-Based Learning Videos for Physical Education Teachers” and is motivated by the digital literacy gap among physical education teachers in the digital 4.0 era, where 40% of teachers have a basic understanding of AI but almost none of them have implemented it in their teaching, while Generation Z and Alpha students need innovative and interactive learning approaches in line with technological developments. The objective of the training is to improve the digital competence of physical education teachers in creating AI-based learning videos, effectively integrating AI technology, and creating interactive learning media to improve the quality of physical education learning. The training was conducted over two days with a theoretical and practical approach by a team from Cenderawasih University, covering four main topics: an introduction to AI in learning, AI tools and applications (Pictory, Lumen5, Synthesia, Descript), steps for making videos, and editing using Kapwing with intensive guidance. The training results showed that 78% of teachers successfully produced at least 2 quality learning videos, 85% of teachers felt more confident in using AI technology, a sustainable learning community was formed with 24 active teachers collaborating, and an AI-based motion analysis system with a response time of 1.8 seconds and 95% cross-device compatibility. The training outcomes included an 83% increase in student engagement, a 12.5% increase in learning outcomes, a transformation of learning from a traditional paradigm to modern adaptive learning, the availability of digital resources in the form of modules, tutorials, and AI application guides, and scientific publications in Sinta-level community service journals. ABSTRAKPelatihan ini berjudul "Pelatihan Pembuatan Video Pembelajaran Berbasis Artificial Intelligence (AI) bagi Guru Penjas" yang dilatarbelakangi oleh kesenjangan literasi digital guru Pendidikan Jasmani di era digital 4.0, dimana 40% guru memiliki pengenalan dasar AI namun hampir seluruhnya belum mengimplementasikannya dalam pembelajaran, sementara siswa generasi Z dan Alpha membutuhkan pendekatan pembelajaran inovatif dan interaktif sesuai perkembangan teknologi. Tujuan pelatihan adalah meningkatkan kompetensi digital guru Penjas dalam membuat video pembelajaran berbasis AI, mengintegrasikan teknologi AI secara efektif, dan menciptakan media pembelajaran interaktif untuk meningkatkan kualitas pembelajaran Pendidikan Jasmani. Pelatihan dilaksanakan selama 2 hari dengan pendekatan teoritis dan praktis oleh tim pengabdi Universitas Cenderawasih, mencakup empat materi utama yaitu pengantar AI dalam pembelajaran, alat dan aplikasi AI (Picstory, Lumen 5, Synthesia, Descript), langkah pembuatan video, dan pengeditan menggunakan Kapwing dengan pendampingan intensif. Hasil pelatihan menunjukkan 78% guru berhasil memproduksi minimal 2 video pembelajaran berkualitas, 85% guru merasa lebih percaya diri menggunakan teknologi AI, terbentuknya komunitas pembelajaran berkelanjutan dengan 24 guru aktif berkolaborasi, dan sistem analisis gerakan berbasis AI dengan waktu respons 1,8 detik serta kompatibilitas 95% lintas perangkat. Luaran pelatihan meliputi peningkatan keterlibatan siswa 83%, peningkatan hasil belajar 12,5%, transformasi pembelajaran dari paradigma tradisional menuju pembelajaran modern adaptif, tersedianya sumber daya digital berupa modul, tutorial dan panduan aplikasi AI, serta publikasi ilmiah di jurnal pengabdian kepada masyarakat level sinta.